Glacial-interglacial variations of the water masses in the southeast Atlantic Ocean derived from foraminiferal neodymium isotope ratios - Von Koslowski, Rebecca (Marine Research (MA-RE) Institute, 2017)
Variations in the global climate over time have long been associated with changes in the meridional overturning circulation of the oceans. It is now commonly believed that, during the Last Glacial Maximum (LGM), the transport of North Atlantic Deep Water (NADW) to the southeast Atlantic Ocean was reduced. A popular method to trace these ambient changes is the stable isotope systematics of neodymium (given as εNd). In this study εNd data were measured on mixed planktic and bulk foraminifera from two gravity cores, GeoB8336-6 and GeoB8342-6, retrieved from the Cape Basin at water depths of 3524 and 3521 meters from the western continental slope of South Africa. The samples were prepared following the protocol presented by the Cambridge group (Tachikawa, Piotrowski, & Bayon, 2014). Planktic and bulk foraminifera samples taken from the same core depth interval had the same εNd ratios within error, which suggests that bulk foraminifera may provide a quick way to reconstruct ambient bottom water values. However, more research is needed to further support these findings. While the Holocene samples' εNd ratios (εNd(N36/6a) -10.7±0.3 and εNd(N42/6a mean) -10.2±0.4) lie within the range of modern Eastern NADW (εNd(modern ENADW) -10.9±1.2), glacial samples yield significantly more radiogenic εNd ratios (εNd(N42/6b) -7.7/ εNd(N36/6b) -8.1). This indicates the greater influence of southern-sourced water masses and thus provides further evidence for a reduction of NADW during the last glacial. MIS3 samples show ratios that lie in between those observed in the LGM and Holocene, and it is hypothesized that ocean circulation during MIS3 was comparable to that during the transition from the LGM to the Holocene (Termination I).